2021
DOI: 10.20473/jbe.v9i22021.202-210
|View full text |Cite
|
Sign up to set email alerts
|

Factor Associated with Underweight among People with Tuberculosis

Abstract: Background: The relationship between Tuberculosis (TB) and nutritional status is a significant one. Patients with TB who are underweight face a higher risk of death. Purpose: This research aims to analyze the factors related to the occurrence of being underweight among TB patients at the Public Health Center (PHC) in Perak Timur, Surabaya. Method: This was an analytical observational study and used a cross-sectional design. The sample for this research was 41 respondents, who were TB patients and were undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…The number of TB AFB+ cases in 2018 was 3,003, with a total cure rate of 2,111 (70.30%) (10). Surabaya confirmed TB AFB+ in 2019 in as many as 2,998 patients, with 2,399 (80.02%) declared cured (11). The number of TB AFB+ patients in 2020 was 4,943, with 2,810 (56.85%) patients declared cured (8), which shows that the cure rate in 2018-2020 is still below the target of 85% of the total incidence of TB AFB+.…”
Section: Tuberculosis (Tb) Is An Airborne Disease Caused By Mycobacte...mentioning
confidence: 94%
See 2 more Smart Citations
“…The number of TB AFB+ cases in 2018 was 3,003, with a total cure rate of 2,111 (70.30%) (10). Surabaya confirmed TB AFB+ in 2019 in as many as 2,998 patients, with 2,399 (80.02%) declared cured (11). The number of TB AFB+ patients in 2020 was 4,943, with 2,810 (56.85%) patients declared cured (8), which shows that the cure rate in 2018-2020 is still below the target of 85% of the total incidence of TB AFB+.…”
Section: Tuberculosis (Tb) Is An Airborne Disease Caused By Mycobacte...mentioning
confidence: 94%
“…The population density in 2018 was 8,841.36 people/km2, meaning that 1 km2 is inhabited by 8,842 people (10). The population density in 2019 was 8,862.01 people/km2, meaning that every 1 km2 is inhabited by 8,862 people (11). The population density in 2020 is 8,888.19 people/km2, meaning that every 1 km2 is inhabited by 8,888 people (8).…”
Section: Tuberculosis (Tb) Is An Airborne Disease Caused By Mycobacte...mentioning
confidence: 99%
See 1 more Smart Citation
“…Status gizi adalah hasil keseimbangan antara asupan nutrisi dengan nutrisi yang dibutuhkan tubuh (3). Status gizi pada pasien TB memiliki hubungan dua arah (4).…”
Section: Aunclassified
“…Furthermore, a study at the East Perak Health Center indicated that the treatment phase can be associated with the weight of Tuberculosis patients. The results of the study showed that individuals in the intensive treatment phase were 2.33 times more likely to experience underweight compared to those in the continuation treatment phase [22]. The dosage of Anti-Tuberculosis Drugs administered to TB patients is carefully regulated to ensure precise dosing in accordance with the TB management guidelines.…”
Section: The Association Between Initial Body Weight At the Start Of ...mentioning
confidence: 99%